MODEL PERENCANAAN DAN PENGELOLAAN LINGKUNGAN BERBASIS MASYARAKAT KASUS : BENTANGLAHAN KAWASAN TEMBALANG SEMARANG - Samadikun, Budi Prasetyo; Sudibyakto, Sudibyakto; Setiawan, Bakti; Rijanta, Rijanta (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2012)
One of mayor requirement in environmental system planning and management is to predict the condition  in  the  future.  Model  can  be  used  to  simplified  the  prediction  and  arrangement  of anything.  There  are  four  steps  as  a  guidance  for  making  a  model,  i.e.:  model  formulation, parameter identification, parameter estimation, and model validation. The result being expected after applying those four steps is a good model that consistent with study objective, simple, and applicable.